Secretarial profession and the changing landscape of business in Nigeria - Bessie, Obuba (Journal of Professional Secretaries and Office Administrators, 2013)
The only constant thing on earth is change. Sometimes, change tends to affect the very foundation of certain phenomenon trying to give it a new face altogether. The Secretarial Profession is not an exception. Science and Technology has changed virtually everything including human behavioural pattern. Man and his business environment have been witnessing changes virtually in every sphere of life. Primitivisms are giving way to modernity in every business set up in order to maintain patronage. This trend poses great challenge to the Secretarial Profession if it must remain relevant to the present day realities. The language is ADAPTATION. This paper seeks to examine the changes in the business landscape in Nigeria especially as brought about by Science and Technology as well as its effects and challenges on the Secretarial Profession.